2001
DOI: 10.1023/a:1010353315939
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We investigated the hypothesis that wood-boring beetles in the genus Monochamus (Cerambycidae) utilize pheromones of sympatric bark beetles as host-finding kairomones. All nine bark beetle pheromones tested electrophysiologically were antenally active for both sexes of M. scutellatus, M. clamator, and M. obtusus from British Columbia. When field-tested with multiple-funnel traps (British Columbia) or cross-vane traps (Ontario), a blend composed of frontalin, ipsdienol, ipsenol, and MCH, in combination with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(12 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…Many species of Coleopteran use tree terpenes as kairomones or pheromones (Byers 1992; Hobson et al 1993; Allison et al 2001, 2004; Thoss and Byers 2006). For instance, the volatile monoterpenes are often found serving as major attractants of Cerambycids (Allison et al 2004), bark beetles (Byers 1992; Hobson et al 1993; Thoss and Byers 2006), and a pine weevil (Nordlander 1990; 1991), or as major chemical cues for natural enemies searching for pine herbivores (Pettersson 2001; Mumm and Hilker 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of Coleopteran use tree terpenes as kairomones or pheromones (Byers 1992; Hobson et al 1993; Allison et al 2001, 2004; Thoss and Byers 2006). For instance, the volatile monoterpenes are often found serving as major attractants of Cerambycids (Allison et al 2004), bark beetles (Byers 1992; Hobson et al 1993; Thoss and Byers 2006), and a pine weevil (Nordlander 1990; 1991), or as major chemical cues for natural enemies searching for pine herbivores (Pettersson 2001; Mumm and Hilker 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some herbivores and natural enemies show chiral specificity in responses to host plant semiochemicals (Miller et al 1996; Wibe et al 1998; Allison et al 2001; Erbilgin and Raffa 2001; Mozuraitis et al 2002; Hull et al 2004). Hobson et al (1993) found that Dendroctonus valens LeConte is strongly affected by the enantiomeric composition of monoterpenes.…”
Section: Discussionmentioning
confidence: 99%
“…The subfamily Lamiinae was targeted by baiting all of the traps with semiochemicals (α-pinene, ipsdienol, and ipsenol) known to be attractive to Monochamus spp. [24], [36][38]. Experiments 5–8 used the same experimental designs [i.e., experiments 1 and 5, 2 and 6, 3 and 7, and 4 and 8 were identical] but targeted the subfamily Cerambycinae by baiting all of the traps with racemic 3-hydroxy-2-hexanone and (2 R *, 3 R *)-hexanediol, two common pheromones for species from this subfamily [26], [39].…”
Section: Methodsmentioning
confidence: 99%
“…Adult sawyer beetles are known to use host volatiles and bark beetle pheromones to locate potential hosts (Allison et al 2001, 2003, 2012a; Pajares et al 2004; Miller and Asaro 2005; but see Fan et al 2010). Females deposit eggs into the phloem through oviposition pits or cracks in the bark and larvae develop in the phloem for 3–4 wk before entering the sapwood to construct U-shaped galleries where pupation will occur.…”
mentioning
confidence: 99%